Prevalence and antimicrobial resistance of Escherichia coli in chicken meat and edible poultry organs collected from retail shops and supermarkets of north western province in Sri Lanka - Ranasinghe, R. A. S. S.; Satharasinghe, D. A.; Anwarama, P. S; Parakatawella, P. M. S. D. K.; Jayasooriya, L. J. P. A. P.; Ranasinghe, R. M. S. B. K.; Rajapakse, R. P. V. J.; Huat, J. T. Y.; Rukayadi, Y.; Nakaguchi, Y.; Nishibuchi, M.; Radu, S.; et al. (Hindawi, 2022)
Escherichia coli is a commensal bacterium that lives in human and animal intestines. Shiga toxin-producing strains of E. coli STECs are responsible for most food-related E. coli infections. Pathogenic E. coli transmits to human bodies due to the consumption of contaminated, raw, or undercooked food. This study was conducted to identify the prevalence of E. coli contamination in edible poultry meat and meat organs in the North Western Province of Sri Lanka. A total of 250 samples consisting of chicken meat (n = 144) and edible organs (n = 106) were collected from retail shops (n = 181) and supermarkets (n = 69), in both Kurunegala and Puttlam districts. The prevalence of E. coli from 250 chicken meat samples was 66.80% (167/250); E. coli prevalence at retail shops (66.85%) was higher than that at supermarkets (66.67%) and was not statistically significant. E. coli prevalence in chicken meat and edible organs was 65.73% and 69.16%, respectively. Molecular confirmation for the positive samples was done through polymerase chain reaction (PCR) using previously designed primers. An antibiotic susceptibility test was performed according to CLSI using nine antibiotics: ampicillin, amoxicillin, chloramphenicol, ceftazidime, ciprofloxacin, cephalexin, erythromycin, gentamicin, and tetracycline. Most isolates were resistant to erythromycin (80.84%) and amoxicillin (76.05%), while the least resistance was observed for gentamicin (4.79%). This study indicates the potential public health risk associated with chicken sold at retail and supermarket levels in the North Western Province of Sri Lanka.